Contribution to the evolution of the Perama Cave (Ioannina, NW Greece). - Ifandi, E.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2013)
This study includes the description of thirty three speleothem types, which were found in the Perama cave, Ioannina, NW Greece, according to the international literature, along with the interpretation of their formation, for the first time in Greece. The detailed study of these speleothems coupled with observations of the way of their formation and their spatial distribution enabled us to suggest that the Perama cave evolved through a sequence of episodes that include dissolution of the host Senonian limestone, collapse of its roof formations, as well as alternating events of formation of stalactitic- and stalagmitic-type speleothems with excess water flow and/or flooding, which resulted in the development of stream formations